Fusion energy: a sustainable pathway to meeting future global energy demands - Gaurav Katoch; Gazal Sharma; Mohammed Alaghbari; Amit Ved; Jatinder Kaur; Asha Rajiv; Abhayveer Singh; Yashpal Yadav; Mohammad Iqbal Khairandish (Discover Sustainability)
Abstract Since the 1930s, scientists have worked to replicate nuclear fusion as a reliable energy source. Fusion energy holds immense promise as a sustainable and virtually limitless solution for power generation. Fusing light nuclei, particularly deuterium and tritium, yields fusion processes that release considerably more energy than fossil fuels and nuclear fission sources. This study examines the merits of fusion energy, emphasising its sustainability advantages, such as little environmental effect and plentiful fuel resources. Recent developments in confinement technologies, like tokamaks and stellarators, have made considerable progress in achieving sustained fusion events. Nonetheless, obstacles persist, especially in maintaining plasma stability and attaining net-positive energy production. This analysis emphasises the necessity of ongoing research and worldwide cooperation to surmount these obstacles and realise the potential of fusion energy for global energy requirements.